Fault diagnosis of a wave energy converter based on ball screw mechanism (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper proposes a fault diagnosis (FD) scheme for the InfinityWEC prototype developed by Ocean Harvesting Technologies AB. This device is a wave energy converter (WEC) mainly composed of a heaving buoy and a power take-off (PTO) system, that includes ball screw mechanisms (BSMs) and electrical generators (EGs).  The purpose of each BSM is to convert the linear motion of the buoy, excited by the sea waves, into rotary motion of an EG. Automated FD is of great importance for reducing the operational costs of WECs related to maintenance, because of their deployment at remote locations and the potential damage produced by seawater. In general, FD in WECs must tackle significant challenges such as the uncertainty of the excitation force produced by the waves, which is not directly measurable, as well as phenomena such as nonlinear viscous drag and restoring forces that also affect the buoy motion. Though BSMs having been studied for quite a long time, their mathematical representation in WEC studies is usually oversimplified.  In this paper, a detailed model of the BSM is used to represent potential faults in BSMs, as well as isolating these faults from others that could affect the motion of the buoy or the EG. Faults that could be present in BSM include wear and pitting. Furthermore, a potential failure that could damage the WEC is given by the possibility of jamming of the spheres inside the BSM. To detect and isolate the faults, the proposed diagnosis scheme is composed of residual generators that use motion measurements of the buoy, wave elevation at the WEC location, estimates of the excitation force, electric measurements of the EGs, and estimates of the angular motion of the screws of the BSMs. The performance of the proposed scheme is verified with numerical simulation of the WEC in MATLAB/Simulink, with the incidence of irregular sea waves, in the presence of different faults.